Ответы и объяснения

Лучший Ответ!
2014-03-12T21:43:37+04:00
(3m-a)(a+3m)-(2a+m)(3a-m)=(3ma+9m^{2} - a^{2} -3am)-(6 a^{2} -2am+3am- m^{2} )=3am+9 m^{2} - a^{2} -3am-6 a^{2} +2am-3am+ m^{2} =10 m^{2} -am-7 a^{2}
 x^{2} +3xy-4xy-12 y^{2} +3xy+ x^{2} -9 y^{2} -3xy=2 x^{2} -xy-21 y^{2}
2014-03-12T21:47:31+04:00
3am+9 m^{2}- a^{2} -3 am-6a^{2} +2am -3am+m ^{2} =10m^{2} -am-7a^{2}

(x-4y)(x+3y)+(x+3y)(3y+x)= x^{2} +3 x y - 4x y -12 y^{2}+3x y+ x^{2}-9y^{2} -3x y=2x^{2}-x y-21y^{2} (^{2} -вторая степень)